The Impact of Automatic Store Replenishment on Retail Technologies and Concepts for the Out-of-Stocks Problem - Angerer, Alfred; SpringerLink (Online service) (Wiesbaden : DUV, 2006)
Companies in the fast moving consumer goods industry increasingly look for technologies to improve customer satisfaction while reducing costs at the same time. A technology allowing to raise the availability of products on the retailers' shelves while providing cost reduction opportunities is automatic store replenishment (ASR). It is an intelligent software that automatically places inventory replenishment orders. Drawing on several interviews and a comprehensive statistical analysis, Alfred Angerer proves the effectiveness of such ASR systems. The following questions are adressed: " Which types of ASR system exist? " What are the exact benefits of ASR systems? " Which variables influence the ASR performance? " Which ASR system is best suited for each product? " How does a company best implement ASR systems?
Research Framework and Design -- Literature Research -- Development of Models -- Quantitative Analysis -- Field Research and Managerial Implications -- Conclusion -- Appendix and References.
Keywords: Business; Production management; Sales management; Trade; Commerce; Business and Management; Trade; Operations Management; Sales/Distribution.; Electronic books